Beyond killing: intra- and interspecific nonconsumptive effects among aphidophagous competitors - Bayoumy, Mohamed H.; Awadalla, Hagar S.; Fathy, Dina M.; Majerus, Tamsin M.O. (Wiley, 2018)
1. Beyond killing, predators have nonlethal effects on their potential prey. Because aphids are highly aggregated, their predators aggregate as well, creating conditions optimal for nonconsumptive effects (NCEs) among competing larvae. Although intraguild predator (IGP) density can alter the balance between conflicting forces, little is known about its effect on competing prey. 2. A partitioned Petri-dish that permitted the passage of signals was used to examine the NCEs between competing stages of similar- or different-sized, conspecific or heterospecific, individuals, on development, survival and reproduction of competing prey. 3. Coccinella undecimpunctata L. larvae suffered developmental and reproductive costs resulting from the presence of conspecific and heterospecific larvae, but showed no impact on their survival. In contrast, larvae of Chrysoperla carnea Stephens and Hippodamia variegata (Goeze) gained developmental benefits, without reproductive costs. Faster development can be construed as adaptive, as it reduces immature mortality. 4. Interestingly, threat-sensitive prey responses appear to be species-specific, regardless of predator density. In a C. carnea larva–H. variegata adult competing system, larvae responded to the threat posed by heterospecific adults, with accelerated development, but suffered reproductive costs. In a C. carnea larva–C. undecimpunctata adult system, no overall development costs in response to heterospecific adults were evident. The only cost was on survival at higher IGP density. Thus, the phenotype induced under H. variegata stress was adaptive for development in aphid colonies, whereas that under C. undecimpunctata stress was not. 5. NCEs are not simple vertical forces affecting prey, but can affect guilds on the same trophic level. Co-release of more than one species and density of these species may adversely increase the aphid populations.